1998
DOI: 10.1021/jf980652v
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Compounds in Supercritical Carbon Dioxide Extracts of Iberian Ham

Abstract: The aim of the present study was to obtain aroma extracts from Iberian ham using supercritical carbon dioxide as the extraction technique of volatile compounds. After extraction, it was concluded that larger numbers and higher concentrations of volatile compounds were achieved at 40 °C temperature and at 0.50 g/mL density (91 atm pressure). Identification of volatile compounds using mass spectrometry yielded 87 and 35 compounds in the extracts obtained at 40 °C (91 atm) and 60 °C (129 atm), respectively. All s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…On the other hand, the limonene is the only one that has been previously described by other authors (Ruiz et al, 1998;Sabio et al, 1998;Timón et al, 1998;Ruiz et al, 1999;Andrés Sáchez-Peña et al, 2005;Ramírez et al, 2007;García-González et al, 2008). In 1998, Sabio et al identified 2-carene and 3-carene.…”
Section: Hydrocarbonsmentioning
confidence: 77%
See 4 more Smart Citations
“…On the other hand, the limonene is the only one that has been previously described by other authors (Ruiz et al, 1998;Sabio et al, 1998;Timón et al, 1998;Ruiz et al, 1999;Andrés Sáchez-Peña et al, 2005;Ramírez et al, 2007;García-González et al, 2008). In 1998, Sabio et al identified 2-carene and 3-carene.…”
Section: Hydrocarbonsmentioning
confidence: 77%
“…The determination of volatile compounds has been made in samples taken from the muscles of any piece (slices), like Biceps femoris, semitendinosus or semimembranosus (García et al, 1991;López et al, 1992;Sabio et al, 1998;Timón et al, 1998;Luna et al, 2006;Andrés et al, 2007;Ramírez y Cava, 2007;García-González et al, 2008). Like in the evolution of glyceride compounds, the volatile compound fraction of subcutaneous and intermuscular fat has been poorly studied or characterized (Timón et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations